A Review of the Research on the Origin and Connotation of the Theory of "When There is Inequality, There is a Cry" - Shen, Jiaying (Journal of Social Science and Humanities, 2024)
Han Yu is a very important figure in the history of Chinese literature and thought. Su Shi of the Song Dynasty once evaluated his contributions as "the rise of literature and the decline of eight generations, and the drowning of the righteous". His theory of 'When there is inequality, there is a cry' is one of the famous poetic theories in ancient China, which has always been highly valued. However, researchers have different opinions on it, and there are also significant differences. This article focuses on the origin and connotation of the theory, and provides a research review based on the research of modern scholars on the concept of "inequality leads to prosperity".